Eye on Korea : an insider account of Korean-American relations - Young, James V., 1941- (Texas A & M University military history series, 2003)
"Colonel James V. Young, one of the American military's first area specialists, spent almost twenty years in Asia, including fourteen in Korea. In this memoir, he writes with the expertise of an old Korea hand about a period that saw South Korea make the transition from an agrarian economy to a modern industrial state." "Young volunteered in 1969 for a new program aimed at creating area specialists within the military. In 1975, after four years of training in Korean language and culture, he witnessed how American diplomats convinced Park Chung-Hee, the South Korean president, not to develop his own nuclear weapons." "Later, from the perspective of a military attache, Young saw the mistrust that characterized U.S.-Korean relations during the 1970s. He provides new insights into the intrigue and behind-the-scenes efforts to derail President Jimmy Carter's troop withdrawal policies, and he argues that the United States was caught flat-footed by such crucial episodes as the coup of 1979 and the arrest of Gen. Chung Sung Hwa in what became known as the 12/12 Incident. He provides on-the-scene observations of the imposition of martial law and the Kwangju incident that followed, when security forces ran amok during protests in the city and killed and wounded hundreds of civilians. Further, his insider account of dealing with North Korean senior leaders in both diplomatic negotiations and business settings makes a unique contribution to understanding the internal dynamics within this secretive state." "Young's memoir straddles the line between military and diplomatic history. Those interested in the region, the issues, and military life off the battlefield will value this book."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved